THE ROLE AND IMPACT OF THIRD-PARTY MEDIATOR IN AN ORGANISATION IN THE 21ST CENTURY NIGERIA - ADEDEJI Amos Ojo (Scholar Express Journal, 2021)
Conflict is normal, natural and inevitable, yet it can generate negative and very destructive impacts. Attempts to respond to conflicts in a constructive way is apt. The attitudes and information at the disposal of peace practitioner dictate the way conflict is manage. Mediation has therefore been seen as an effective platform of managing conflict. The study examines the role and impact of mediator in organisation (society). The paper adopts content analysis by limiting the data collection to secondary source. The study found out that the entire process of mediation could be viewed as a peaceful and long lasting model of conflict resolution in the 21st century. It revealed that mediation process is hindered by number of challenges such as lack of mediation acts, lack of adequate training and lack of documentation for reference purpose to mention a few. The study recommends proper orientation and dissemination of activities of mediation and other ADR mechanisms to the citizens by the government among others.
Keywords: Conflict; Third Party; Mediation; Organisation